Factors of attractiveness of public service for young specialists in the conditions of modern Russia ("Journal "U". Economy. Management. Finance.", 2024)
The present study examines the factors that young specialists are most interested in employers. In the conditions of modernity, the whole labor market is experiencing a shortage of specialists, including young specialists, and the civil service does not become an exception in this situation. Within the framework of the study of the existing situation the correlation between the conditions offered by the labor market and the desires of young people is carried out, and a number of key problems are deduced.
Keywords: youth; attractiveness factor; civil service; labor conditions